Renal Myxoma in a Feline - da Silva, Thayná Oliveira; Zuliani, Fernanda; Rocha, Noeme Sousa; Fonseca Alves, Carlos Eduardo (Acta Scientiae Veterinariae, 2019)
Background: Renal neoplasms are a rare condition in felines, with metastatic lymphoma presenting the highest incidence rate. Secondary renal neoplasms are more frequent (88%) than primary renal tumors, with primary mesenquimal renal neoplasms accounting for 22% of the cases and the incidence of benign tumors not exceeding 5%. Myxomas are neoplasms in undifferentiated mesenchymal cells with abundant reproduction of the myxoid matrix, with few few case reports about this type of neoplasm in the veterinary literature. This study reports the first case of renal myxoma in a young feline afflicted by granulomatous nephritis and diagnosed with FIP (Feline Infectious Peritonitis). Case: A 9-month-old, male, mixed breed feline, was admitted into the Veterinary Hospital maintained by the School of Veterinary Medicine and Animal Science, Botucatu, Brazil, presenting symptoms such progressive weight loss and occasional episodes of emesis for one week, progressing to anorexia, hematochezia, vocalization, lack of coordination, spasms, anuria and inability to defecate. A physical examination revealed moderate dehydration, low temperatures (< 33ºC), dyspnea (36 mpm), slight hyperglycemia (187 mg/dL) and distension of the abdomen and of the urinary bladder. The hematological assay and the serum biochemistry assay revealed neutrophilic leukocytosis, thrombocytopenia, anemia and slight uremia. In view of the severity of the neurologic signs and lack of response to the clinical treatment, the owner opted to euthanize the animal. The necropsy revealed diffused jaundice, with kidney injuries observed through the pale coloration of the tissue and irregular surface with multiple off-white small nodules distributed in a marked and diffuse way. The same injury pattern was observed markedly in the lungs and discretely in the spleen and liver. The material collected was fixed in a 10% formalin solution, and processed according to the routine technique (Hematoxylin & Eosin). The remaining samples were submitted to a histochemical analysis with the Alcian Blue and Masson’s Trichrome stains, in addition to an immunohistochemical expression test. The histopathological examination with H&E staining revealed multiple focuses of pyogranulomatous injuries in the kidneys, lungs, spleen, uvea and leptomeninges, corroborating the diagnosis of feline infectious peritonitis (FIP). In addition, there was a neoplastic proliferation of fusiform cells among an abundant myxoid matrix, evident in Alcian Blue staining. Normal renal tissue, such as glomeruli or tubules, were occasionally observed inside the neoplastic proliferation. Masson’s Trichrome technique was used to exclude the possibility of a fibroblastic origin. In addition, immunohistochemistry (IHC) was performed to confirm the diagnosis of myxoma using the Vimentin, pan-cytokeratin and p63 antibodies. Discussion: Kidney tumors are rare in veterinary medicine, but have an incidence rate four to five times greater in cats than in dogs. The veterinary literature describes myxomas located in joints, cardiac valves and ureter, but reports of myxomas afflicting the kidneys are more commons in human medicine. This tumor should be included in the differential diagnosis process for young cats with suspicions of renal neoplasms, however, to differentiate between neoplasms with a myxoid component in benign tumors. This is the first reported case of renal myxoma afflicting a young feline with feline infectious peritonitis (FIP) in the veterinary literature.